Eligibility Criteria of Participants in Randomized Controlled Trials Assessing Conservative Management of Cervical Radiculopathy: A Systematic Review. Issue 10 (15th May 2023) - Plener, Joshua; da Silva-Oolup, Sophia; To, Daphne; Csiernik, Ben; Hofkirchner, Corey; Cox, Jocelyn; Chow, Ngai; Hogg-Johnson, Sheilah; Ammendolia, Carlo
Abstract : Study Design: Systematic review. Objective: The aim of this study was to evaluate the inclusion and exclusion criteria for participants in randomized control trials (RCTs) assessing conservative management for cervical radiculopathy (CR), to determine if any consensus exists within the literature. Summary of Background Data: A 2012 systematic review identified a lack of uniformity for the eligibility criteria of participants in RCTs evaluating conservative interventions for CR. Since then, a large number of RCTs have been published, signaling the need for an updated evaluation of this topic. Materials and Methods: We electronically searched MEDLINE, CENTRAL, CINAHL, Embase, and PsycINFO from inception to June 15, 2022, to identify RCTs assessing conservative management of CR. Information extracted was analyzed to determine the level of homogeneity and/or heterogeneity of the inclusion and exclusion criteria across studies. Results: Seventy-six RCTs met our inclusion criteria with 68 distinct trials identified. The inclusion of arm pain with or without another symptom ( i.e. numbness, paresthesia, or weakness) was required in 69.12% of trials, 50% of trials required participants to exhibit neck symptoms, and 73.53% of studies required some form of clinical examination findings, but inconsistencies existed for the number and type of tests used. Furthermore, 41.18% of trials included imaging, with 33.82% of trials requiring magnetic resonance imaging findings. The most common exclusion criteria included were the presence of red flags and cervical myelopathy in 66.18% and 58.82% of trials, respectively. Conclusions: Overall, there is still a lack of uniformity for the inclusion/exclusion criteria of trials assessing the conservative management of CR, with some improvements noted compared with the 2012 review. Based on the current literature assessing the diagnostic utility of clinical symptoms and confirmatory tests, we proposed inclusion criteria for trials assessing conservative interventions. Future research should aim to develop standardized classification criteria to improve consistency among studies.